ELEVENTH GRADE STUDENTS’ PERFORMANCE IN WRITING DESCRIPTIVE TEXTS AT SMK N 1 KASIHAN BANTUL - Ludovikus Ludovikus (Journal of English Language Learning, 2018)
This study was conducted to find out: (a) How is the students’ performance in writing descriptive texts and (b). What are the factors that affect the students’ performance in writing descriptive texts?The researcher used case study; the data employed were classroom observation, interview, the task and documentation. The collected data were analyzed descriptively. The validity and reliability of the data were conducted by applying the protocol analysis.Findings show that students’ performance in writing descriptive texts was various. Some students preferred to write the texts spontaneously. Almost all the students said that they did not make the outline and draft before writing. They stated that they made the revision, topic sentence, arrangement of words and some of them did not develop the idea. The factors that affect students’ performance were difficulty in vocabulary,  grammar and the arrangement of the text in the paragraph and grammatical structure.